Implementasi Kurikulum PAI Terpadu dengan Kurikulum Pondok Pesantren untuk Meningkatkan Prestasi Belajar Siswa - Sobandi, Deni; Sukandar, Ahmad; Setiawan, Marwan (CV. Media Publikasi Profesional, 2022)
The problem behind this research is that there is a separation between schools that are general and schools that have more religious lessons, from the findings in the field of implementing the Integrated Islamic Education curriculum with Islamic boarding schools to improve student achievement. An institution, of course, must use the management theory of findings from this research, among others: in planning some Islamic boarding school teachers are still passive so they do not provide opportunities for students to be active and creative, this is because the pesantren teachers do not understand the media and learning models used. This study aims to find ways and evidence for the implementation of an integrated PAI curriculum with Islamic boarding schools to improve student achievement in this study using a qualitative paradigm. This research is based on a theory regarding the implementation of an integrated curriculum in improving student achievement which includes the understanding, principles, benefits, objectives, and management of an integrated PAI curriculum to improve student achievement with qualitative research methods, through interviews, observations, and documentation studies. The results of the study show that: (1) planning the implementation of an integrated PAI curriculum to improve student achievement by outlining the syllabus, which is designed and then described in the lesson plans as a lesson plan in the classroom, (2) implementing the implementation of an integrated PAI curriculum in improving student achievement. with preliminary activities that function to create an effective learning atmosphere, (3) evaluation of the implementation of the integrated PAI curriculum to improve student achievement is reflected in the results of field observations, namely evaluation of learning outcomes carried out by written and oral tests, (4) supporting factors in curriculum implementation PAI is integrated with Islamic boarding schools to improve student achievement including daily religious activity programs starting from the Asmaul Husna apple, joint duha, joint tadarus and juhur prayers in congregation, while the inhibiting factors include: an Integrated PAI teacher who is less capable in the learning process. The conclusion is that teachers must fix the planning and implementation of learning and evaluations carried out, must be able to change learning outcomes, and provide opportunities for students to actualize the potential that exists in themselves so that student achievement increases.